2006
DOI: 10.1111/j.1365-2958.2006.05524.x
|View full text |Cite
|
Sign up to set email alerts
|

σE‐dependent small RNAs of Salmonella respond to membrane stress by accelerating global omp mRNA decay

Abstract: Summary The bacterial envelope stress response (ESR) is triggered by the accumulation of misfolded outer membrane proteins (OMPs) upon envelope damage or excessive OMP synthesis, and is mediated by the alternative sigma factor, σE. Activation of the σE pathway causes a rapid downregulation of major omp mRNAs, which prevents further build‐up of unassembled OMPs and liberates the translocation and folding apparatus under conditions that require envelope remodelling. The factors that facilitate the rapid removal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
412
2
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 336 publications
(429 citation statements)
references
References 68 publications
(130 reference statements)
14
412
2
1
Order By: Relevance
“…2.24a,b). To confirm Dual RNA-seq-based gene expression profiling of intracellular Salmonella by unrelated methods, four of the induced sRNAs were selected for independent qRT-PCR experiments: The wellcharacterized Salmonella sRNAs RyhB (Masse and Gottesman, 2002) and RybB (Balbontin et al, 2010;Papenfort et al, 2006) were chosen as representative for a highly (>100 fold) or slightly (~2 fold) induced sRNA. In addition, STnc440 -a previously validated (Sittka et al, 2008) but poorly characterized sRNA -was included as was a computationally predicted candidate sRNA, STnc510.…”
Section: Srna Expression Profile Of Intracellular Salmonellamentioning
confidence: 99%
See 2 more Smart Citations
“…2.24a,b). To confirm Dual RNA-seq-based gene expression profiling of intracellular Salmonella by unrelated methods, four of the induced sRNAs were selected for independent qRT-PCR experiments: The wellcharacterized Salmonella sRNAs RyhB (Masse and Gottesman, 2002) and RybB (Balbontin et al, 2010;Papenfort et al, 2006) were chosen as representative for a highly (>100 fold) or slightly (~2 fold) induced sRNA. In addition, STnc440 -a previously validated (Sittka et al, 2008) but poorly characterized sRNA -was included as was a computationally predicted candidate sRNA, STnc510.…”
Section: Srna Expression Profile Of Intracellular Salmonellamentioning
confidence: 99%
“…Thus, in order to identify direct targets of this sRNA, a previously described pulse-expression approach was applied (Masse et al, 2005;Papenfort et al, 2006). Briefly, the sRNA of interest is transiently over-expressed for a short time period (5-10 min) from an arabinose-inducible promoter and the global abundance of mRNAs is monitored in the presence or absence of the sRNA.…”
Section: Pulse-expression Experiments Identify Stnc440 Targetsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tjaden et al (2006) suggested that functional relationship of the proteins encoded by target candidates, as it is also seen among the GcvB targets, may add confidence to predictions. Similarly, the OmrA/B and RybB sRNAs were predicted to directly target multiple mRNAs that collectively encode for outer membrane proteins Johansen et al 2006;Papenfort et al 2006). By the same token, the iron stress-responding E. coli RyhB sRNA was shown to regulate multiple mRNAs that encode proteins involved in iron metabolism (Massé and Gottesman 2002), and many of the mRNAs demonstrated to be direct targets of S. aureus RNAIII encode bacterial virulence factors (Boisset et al 2007).…”
Section: Gcvb Targets Multiple Transporter Mrnas Genes and Development mentioning
confidence: 99%
“…Recent biocomputational and experimental approaches predicted more sRNAs to target multiple mRNAs. For example, pulse expression of several E. coli and Salmonella sRNAs (Massé et al 2005;Guillier and Gottesman 2006;Johansen et al 2006;Papenfort et al 2006;Tjaden et al 2006) followed by global transcriptome profiling showed the rapid depletion of many mRNAs. The kinetics of target decay observed in these experiments strongly argues that the regulated mRNAs are direct targets.…”
mentioning
confidence: 99%